Use of pressure manifestations following the water plasma expansion for phytomass disintegration - Maroušek, Josef; Kwan, Jason Tai Hong (Water science and technology, 2013)
A prototype capable of generating underwater high-voltage discharges (3.5 kV) coupled with water plasma expansion was constructed. The level of phytomass disintegration caused by transmission of the pressure shockwaves (50-60 MPa) followed by this expansion was analyzed using gas adsorption techniques. The dynamics of the external surface area and the micropore volume on multiple pretreatment stages of maize silage and sunflower seeds was approximated with robust analytical techniques. The multiple increases on the reaction surface were manifest in up to a 15% increase in cumulative methane production, which was itself manifest in the overall acceleration of the anaerobic fermentation process. Disintegration of the sunflower seeds allowed up to 45% higher oil yields using the same operating pressure.
Keywords: Helianthus; Zea mays; tlak; Biomass; Electricity; Pressure; Water; Biofuels; elektřina; biopaliva; biomasa; voda; kukuřice setá